2022
DOI: 10.1063/5.0082562
|View full text |Cite
|
Sign up to set email alerts
|

Generative modeling of turbulence

Abstract: We present a mathematically well-founded approach for the synthetic modeling of turbulent flows using generative adversarial networks (GAN). Based on the analysis of chaotic, deterministic systems in terms of ergodicity, we outline a mathematical proof that GAN can actually learn to sample state snapshots from the invariant measure of the chaotic system. Based on this analysis, we study a hierarchy of chaotic systems starting with the Lorenz attractor and then carry on to the modeling of turbulent flows with G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Our previous work [5] showed that the application of generative learning for deterministic ergodic systems proves to be a mathematically well-founded approach since it converges in the limit of large observation time. Below, we briefly recapitulate the notion of ergodicity for better understanding and explain the mathematical foundations of conditional generative learning for ergodic systems.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work [5] showed that the application of generative learning for deterministic ergodic systems proves to be a mathematically well-founded approach since it converges in the limit of large observation time. Below, we briefly recapitulate the notion of ergodicity for better understanding and explain the mathematical foundations of conditional generative learning for ergodic systems.…”
Section: Methodsmentioning
confidence: 99%
“…We compare GAN synthesized and LES turbulence by quantities that can be cast in an abstract form E x∼µ [ψ(x)] of ( 2) and (3) given a certain evaluation function ψ. Our previous work [5] shows that this approach is reasonable since any statistic evaluated on GAN synthesized flow fields converges on average to the corresponding statistic evaluated on LES data in the limit of large data and large network capacity, which makes this convergence uniform over all uniformly bounded functions ψ.…”
Section: Physics-based Evaluation Metricsmentioning
confidence: 99%
See 3 more Smart Citations